Construção de vocabulário controlado multilíngue : um estudo de possibilidades no contexto da garantia cultural e pela perspectiva da terminologia - Biscalchin, Ricardo (2013)
Identifies parameters for building multilingual controlled vocabularies of union catalogs of university libraries in the cultural context of the cultural warranty, compared to theoretical and methodological assumptions of Terminology and interdisciplinary field of Knowledge Representation and Organization. Therefore, it has been the aim of contributing to the dissemination of scientific knowledge and visibility nationally and internationally, through the use of multilingual controlled vocabulary, allowing the search and retrieval of information in different geographies and cultures to generate new knowledge applicable to the welfare of society, allowing equal representation and retrieval of information in the most distinct languages and cultures. The universe of this research are the information units, focusing on university libraries. The methodology consisted of a theoretical study on the identification and selection of parameters for building multilingual controlled vocabularies before the theoretical areas of Information Science, with emphasis on ensuring cultural and of the Terminology, through dialogue with the field of translation. As a result, we have established fourteen parameters for building multilingual controlled vocabularies that include respect for minorities and cultural differences and terminology present in different languages, among others aspects It is concluded that the establishment of parameters for building multilingual controlled vocabularies in the context of the cultural warranty and the perspective of Terminology contributes to the thematic representation information from culturally terms consistent among the different languages that compose it.